Living without Sanitary Sewers in Latin America : The Business of Collecting Fecal Sludge in Four Latin American Cities - Rojas Ortuste, Franz (World Bank, Washington, DC, 2014)
The present report spotlights the major challenges and the opportunities that lie ahead in fecal sludge management and summarizes the findings from four case studies that describe the current and potential market for sludge removal, collection, and disposal in peri-urban areas. These areas, inhabited by a variety of ethnic, religious, and cultural groups, typically struggle with high population density, insufficient land use planning, high citizen insecurity, and low coverage with basic services. The report demonstrates how technical, financial, environmental, social, regulatory, political, and institutional factors interact to create supply and demand in four markets where coverage with sanitary sewerage services is below the regional average, namely: Santa Cruz (Bolivia), Guatemala City (Guatemala), Tegucigalpa (Honduras), and Managua (Nicaragua).